Cuidado de si e a produção de artesãos de vida : narrativas no campo da saúde mental - Dadalto, Carolina Fonseca (2011)
This work was developed through the problematization of practices in the field of Mental Health, considering the historical and political context of the Psychiatric Reform. The question that guided this study worked was the concept – a tool proposed by Michel Foucault, entitled Self Care , Foucault based on Greek thinking. He proposes Self Care as a constant exercise, as an attitude - for himself, to others, to the world, a form of attention. In order to problematize / think about the care practices available to users of mental health services and taking as reference the notion of Self Care, we have used cartography as a methodological strategy. Thus, we have followed the daily life of a mental health service within Espírito Santo State, Brazil. We have used the narrative of Walter Benjamin to tell about the events experienced. The stories told in this study helped us in the exercise of thinking about what we have helped people to learn with our professional practices. What ways of life have been helped in these spaces? And beyond these spaces? Which speeches have been learned and permeated with these practices? Meetings that have happened during this study showed that: thinking about the Self Care as the relational order, stating that all participants of the relationship suffer affectations, and we are all somehow involved in the relationships we have established, there is such a challenge to the routine of services, considering how professional relationships have been established in the current socio-economic-political. Thus, we believe that is necessary, therefore, an analysis of the implications of the subjects that are present in relationships, and a mapping which has the forces permeate flows. And though these tests can be established with the subjects with which we relate practices that enhance them and their lives. We understand that thinking about the Self Care at the mental health services and consider the lives that are there for them is to think beyond those areas, since they need to act as devices, or as triggers of other ways of living the verbs of life.